Older age and type of surgery predict the early inflammatory response to hip trauma mediated by interleukin-6 (IL-6) - Sedlář, Martin; Kovářová Kudrnová, Zuzana; Erhart, David; Trča, Stanislav; Kvasnička, Jan; Krška, Zdeněk; Mazoch, Jiří; Malíková, Ivana; Zeman, Miroslav; Linhart, Aleš (Archives of gerontology and geriatrics, 2009)
Hip trauma and surgery are associated with systemic inflammatory reaction. However, little evidence exists about the role of IL-6. In order to assess the inflammatory response, we evaluated white blood cell (WBC) count, C-reactive protein (CRP) and IL-6 dynamics in sequential pre- and postsurgical samples collected from 125 elderly patients (mean age 78+/-9 years) undergoing osteosynthesis (OS) for extracapsular hip fractures (n=69), hemiarthroplasty (HA) or urgent total hip arthroplasty for intracapsular fractures (UA) (n=35), and elective total hip arthroplasty for osteoarthrosis (OA) (n=21). Both preoperative CRP and IL-6 levels were higher in patients with intracapsular fractures. IL-6 levels reached peak values immediately after the surgery, while CRP peak levels were reached 48 h after the surgery. The overall inflammatory reaction was more intense in HA patients compared to the other subgroups. Independent of each other, older age and the hip fracture type affected the IL-6 response, while the CRP response depended only on the type of surgery. The abrupt increase in IL-6 immediately after the procedure suggests its involvement in the early stages of the postoperative inflammatory reaction after hip surgery. This reaction is particularly pronounced in elderly patients receiving HA.
Keywords: zánět; Female; fraktury kyčle; ženské pohlaví; chirurgie operační; lidé; pooperační komplikace; Interleukin-6; míra přežití; Inflammation; Male; Postoperative Complications; Aged; interleukin-6; Survival Rate; senioři; mužské pohlaví; Surgical Procedures, Operative; Hip Fractures; Humans